An intronic GAA repeat expansion in FGF14 causes the autosomal-dominant adult-onset ataxia SCA50/ATX-FGF14 - Rafehi, Haloom; Read, Justin; Szmulewicz, David J; Davies, Kayli C; Snell, Penny; Fearnley, Liam G; Scott, Liam; Thomsen, Mirja; Gillies, Greta; Pope, Kate; Bennett, Mark F; Munro, Jacob E; et al. (American journal of human genetics, 2023)
Adult-onset cerebellar ataxias are a group of neurodegenerative conditions that challenge both genetic discovery and molecular diagnosis. In this study, we identified an intronic (GAA) repeat expansion in fibroblast growth factor 14 (FGF14). Genetic analysis of 95 Australian individuals with adult-onset ataxia identified four (4.2%) with (GAA) and a further nine individuals with (GAA) . PCR and long-read sequence analysis revealed these were pure (GAA) repeats. In comparison, no control subjects had (GAA) and only 2/311 control individuals (0.6%) had a pure (GAA) . In a German validation cohort, 9/104 (8.7%) of affected individuals had (GAA) and a further six had (GAA) , whereas 10/190 (5.3%) control subjects had (GAA) but none were (GAA) . The combined data suggest (GAA) are disease causing and fully penetrant (p = 6.0 × 10 , OR = 72 [95% CI = 4.3-1,227]), while (GAA) is likely pathogenic with reduced penetrance. Affected individuals had an adult-onset, slowly progressive cerebellar ataxia with variable features including vestibular impairment, hyper-reflexia, and autonomic dysfunction. A negative correlation between age at onset and repeat length was observed (R = 0.44, p = 0.00045, slope = -0.12) and identification of a shared haplotype in a minority of individuals suggests that the expansion can be inherited or generated de novo during meiotic division. This study demonstrates the power of genome sequencing and advanced bioinformatic tools to identify novel repeat expansions via model-free, genome-wide analysis and identifies SCA50/ATX-FGF14 as a frequent cause of adult-onset ataxia.